STRATEGIC CHALLENGES OF MULTI-SIDED INTERNET START-UPS - Mucha, Tomáš (2012)
The theory of this thesis focuses on particulars of multi-sided platform businesses with special emphasis put on early stage start-ups. The goal is to capture crucial findings and fuse them together to point out specifics which apply only for start-ups that are developed in form of multi-sided platform business. This thesis should provide guidance to all entrepreneurs considering such new business formations. It aims at showing them the most important points leading to positive value creation in multi-sided platform businesses. Specifically, it explains the strategic points hidden behind pricing and network effects utilization. At the same time it depicts what are the unnecessary distractions which just destroy attention and consume time and effort. Consequently, these findings are tested on practical example, where real start-up is modelled using this theoretical framework. Such real application points out strong and weak points. Consequently, the optimal framework is derived based on prior findings. The main suggestions point out what should be examined further by the theory and where the research captured enough knowledge.